Bedfellows, Hostages, or Perfect Strangers? : Global Capital Markets and the Catalytic Effect of IMF Crisis Lending - Giannini, Curzio (IMF Working Papers; Working Paper ;, 2002)
During the 1990s, the concept of "catalytic official finance" (COF) gained prominence in policy debates. The concept revolves around the idea that the propensity of investors to lend to a country increases when the IMF provides its "seal of approval"-backed up by only limited official financing-on the country's economic program. COF aims at avoiding, on the one hand, the massive use of public money to bail out private investors; on the other, the recourse to coercive bailing-in mechanisms. The paper concludes that COF, while possibly useful in other contexts, is less reliable when used to manage capital account crises.